(untitled) (Physical Education, Health and Social Sciences, 2025)
Health is essential for the common man in general and for the sportsmen in particular. Weightlifting is an intense sports, since competitors draw on all their mental and physical strength to lift massive weights, often more than twice their own body weight. Vitamin is an organic compound, the need of which is fulfilled automatically, but due to odd selection of food, deficiencies of the vitamins persist, environmental conditions and health effects vitamins are required to be taken orally. The objective of the current study is to examine the effect of Alfacalcidol supplementation on change serum calcidiol level on bone muscle strength of female weightlifters of Pakistan through change in their best weightlifting capacity and serum calcidiol level after supplementation of Tab. Cadla containing Alfacalcidiol 0.5mcg for a period of 4 months in different groups of female weightlifters of Pakistan using pre-test post-test analysis. Paired sample t-test was used to measure the mean change in best weightlifting capacity and serum calcidiol level (ng/ml) whereas serum calcidiol was measured using LIAISON® 25 OH Vitamin D Total (Kit No. 310600) through Liquid Chromatography-tandem Mass Spectrometry (LC-MS/MS) methods. Overall results showed that there is an escalation in serum calcidiol level cause an increase in the lifting best total of female weightlifting players which cause an increase in their weight lifting capacity and muscular strength due to supplementation of Tab. Cadla (0.5mcg).